PENERAPAN MESIN PENGEPRES KRUPUK SPIRAL UNTUK MENINGKATKAN EFFISIENSI DAN KAPASITAS PRODUKSI KRUPUK PADA INDUSTRI KECIL - I K, Adi Atmika; Karohika, I M. Gatot; Suryawan, Igp A. (Buletin Udayana Mengabdi; Vol 10 No 1 (2011): Volume 10 No.1 – April 2011, 2012)
The process of producing krupuk traditionally passes some steps because it is still used the manual or conventional utensils, however the pressing step requires more sufficient time. Method used to overcome the above problems is by designing and making a machine of semiautomatic pressing row material. This machine is regulated by the electromotor transmission through belt which is fastened upon by pulley, and the rotation is reduced by gear with ratio 50: 1 to get the low rotation at primary axis. This designed machine can make a move to shuffle through as the wanted process. This community service activity was conducted for a group business of krupuk owned by Made Santa in Batubulan village on 25th and 27th August 2009. This Machine application turned out to improve the production capacities reaching 400 %.